Metabolic effects of breastfeeding in women with previous gestational diabetes diagnosed according to the IADPSG criteria. (17th January 2019) - Corrado, Francesco; Giunta, Loretta; Granese, Roberta; Corrado, Silvia; Micali, Marina; Santamaria, Angelo; D'Anna, Rosario; Di Benedetto, Antonino
Abstract: Background: Some studies have already investigated about the short-term favorable metabolic effects of breastfeeding in women with previous gestational diabetes mellitus (GDM). Aim: The aim of our study is to confirm whether the positive effects reported are maintained in the larger cohorts of patients with mild form of gestational diabetes mellitus (GDM) because recently diagnosed according to IADPSG criteria. Materials and methods: This retrospective study includes 97 evaluable consecutive women with prior GDM who have the follow-up oral glucose tolerance test at least 3 months after delivery. Fasting and 2-h plasma glucose values, homeostasis model assessment (HOMA-IR), total cholesterol, and triglycerides were obtained in pregnancy and during the post-partum control. Results: These patients were divided in 81 (83.5%) who lactate until 3 months and 16 (16.5%) who did not lactate. During pregnancy, there are no significant differences between the two groups for age, BMI, fasting and 2-h plasma glucose values, HOMA-IR, total cholesterol and triglycerides. At the postpartum control, we have at univariate analysis significant differences for all these parameters except total cholesterol. After adjustment for confounders we still have, in the breastfeeding group, HOMA-IR reduction (OR 0.370; 95% CI 0.170–0.805; p  < .01) as significant independent variable, whose improvement is the most acknowledged important factor for the prevention of abnormal glucose tolerance later in life. Conclusion: These encouraging results confirm our determination to warmly advice the women affected by GDM to breastfeeding at least for 3 months.